The Human Exersome Initiative (HEI): Rationale, study design, and protocol - Daria Neyroud; Julia Primavesi; Guia Tagliapietra; Chantal Daucourt; Hector Gallart-Ayala; Raphael Gottardo; Julijana Ivanisevic; Aaron L. Baggish (PLoS ONE, 2025)
Habitual physical activity and exercise training (PA/EX) confers numerous health-benefits. Phenotypic adaptations and clinical health outcomes attributable to PA/EX are well-established, and molecular markers and mediators of the PA/EX response have been described. To date, the majority of prior work focused on the biochemical response to PA/EX has leveraged convenience samples of trained athletes participating in events, patients undergoing clinically indicated exercise stress testing, or laboratory protocols comprised of a single dose of exercise. Accordingly, the impact of “exercise dose”, defined by the product of intensity, duration, modality, and frequency, on the human biochemical response to PA/EX remains largely unexplored. The Human Exersome Initiative (HEI) was designed to fill this scientific knowledge gap. Specifically, the HEI will couple carefully controlled laboratory-based acute exercise testing with comprehensive systemic biochemical profiling to isolate the impact of PA/EX duration and intensity on human biochemistry. Herein, we describe the initial phase of the HEI which will aim to comprehensively define the impact of “exercise dose” on blood-based biochemistry in healthy young men and women. The overarching goal of the HEI is to elucidate how the human exercise response varies as a function of phenotypic variability. Using comparator data derived from young men and women, future iterations of this protocol will seek to determine how key sources of human variability (i.e., age, ethnicity, and the presence of comorbid disease) impact the biochemical response to PA/EX. We anticipate results from this work will facilitate biomarker discovery, the elucidation of molecular pathways and mechanisms associated with metabolic responses to exercise, and the identification of optimal exercise doses for future clinical interventions (i.e., tailoring preventive and therapeutic strategies).